2019
DOI: 10.1103/physrevb.100.014105
|View full text |Cite
|
Sign up to set email alerts
|

On-the-fly machine learning force field generation: Application to melting points

Abstract: An efficient and robust on-the-fly machine learning force field method is developed and integrated into an electronic-structure code. This method realizes automatic generation of machine learning force fields on the basis of Bayesian inference during molecular dynamics simulations, where the first principles calculations are only executed, when new configurations out of already sampled datasets appear. The developed method is applied to the calculation of melting points of Al, Si, Ge, Sn and MgO. The applicati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
315
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(379 citation statements)
references
References 66 publications
(97 reference statements)
5
315
0
Order By: Relevance
“…Podryabinkin et al showed that their approach can identify various existing and hypothetical boron allotropes 20 . Finally, Jinnouchi et al demonstrated how ab initio molecular dynamics (AIMD) simulations of specific systems can be sped up by active learning of the computed forces (in a modified GAP framework), using the predicted error of the Gaussian process to select new datapoints and to improve the speed of AIMD 37,39 .…”
Section: Introductionmentioning
confidence: 99%
“…Podryabinkin et al showed that their approach can identify various existing and hypothetical boron allotropes 20 . Finally, Jinnouchi et al demonstrated how ab initio molecular dynamics (AIMD) simulations of specific systems can be sped up by active learning of the computed forces (in a modified GAP framework), using the predicted error of the Gaussian process to select new datapoints and to improve the speed of AIMD 37,39 .…”
Section: Introductionmentioning
confidence: 99%
“…We also mention on-the-fly or "onlinetrained" ML potentials: [80][81][82] these start with a quantummechanical (again, normally DFT-based) MD simulation and train an ML potential while the simulation is being run. We also mention on-the-fly or "onlinetrained" ML potentials: [80][81][82] these start with a quantummechanical (again, normally DFT-based) MD simulation and train an ML potential while the simulation is being run.…”
Section: Ingredient 3: Regression Tools and Implementationsmentioning
confidence: 99%
“…We conclude this methodological overview by stressing that all methods discussed here lead to "offline-trained" ML potentials: one generates (and extensively validates) a suitable potential for a specific material, and then applies it without further modification. We also mention on-the-fly or "onlinetrained" ML potentials: [80][81][82] these start with a quantummechanical (again, normally DFT-based) MD simulation and train an ML potential while the simulation is being run. Numerical measures are put in place to monitor the degree of extrapolation (that is: do we need additional data at this point?…”
Section: Ingredient 3: Regression Tools and Implementationsmentioning
confidence: 99%
“…They benchmark the accuracy of the uncertainty prediction by maximum likelihood estimation which in turn can correct for correlations between resampled models and improve performance of the uncertainty estimation via a cross-validation procedure [120]. By tracking model uncertainty during the MD simulation, a call to the high-fidelity (but expensive) DFT calculation can made when the system drifts to a configuration where the model is uncertain in the energy/force prediction beyond a certain threshold [102,121,122]. Vandermause et al [123] sampled structures on-the-fly from AIMD and used an adaptive Bayesian inference method to automate the training of low-dimensional multiple element interatomic force fields.…”
Section: Iterative Improvement Of Ff Using Active and Transfer Learningmentioning
confidence: 99%